Silicon-containing inherent flame-retardant polyamide 6 with anti-dripping via introducing ethylene glycol as the chain-linker and charring agent. (March 2020) - Fan, Shuo; Zhu, Chenchen; Wu, Dequn; Wang, Xueli; Yu, Jianyong; Li, Faxue
Abstract: An inherent flame-retardant PA6 (FR-PA6) containing polydiphenylsiloxane (PDPS) was synthesized under the action of ethylene glycol (EG) via a facile "2-step" bulk polymerization. Inspiringly, EG acted not only as a 'chain-linker' to connect PA6 oligomer with PDPS moiety but also as a charring agent to increase the charring capacity of FR-PA6 after combustion. The prepared FR-PA6 reached 28.3% of limiting oxygen index (LOI), and passed the V-0 level of UL94 test with suppressed melt-dripping. After investigating the char residues and pyrolysis volatiles of FR-PA6 after combustion, the formation of silicon-rich protective layer was proved to be the essential factor to increase the flame retardancy of FR-PA6 via reducing the diffusion of pyrolysis volatiles, restricting the heat transfer and mass loss as well as preventing polymer melts from dripping. This work thus makes a worthwhile contribution to the development of FR-PA6 by offering a novel route that is easily accessible to industrial fabrication. Highlights: A silicon-containing flame-retardant polyamide 6 (FR-PA6) was first prepared under the assistance of ethylene glycol (EG). EG acted as a chain-linker and charring agent simultaneously. FR-PA6 presented good flame retardancy with anti-dripping performance.